EFFECT OF SUPEROXIDE DISMUTASE AND CATALASE SUPPLEMENTATION IN SOYA MILK EXTENDER ON BUFFALO POST-THAW SEMEN QUALITY - NEHRU, DA; JAN, MH; KUMAR, S; SHARMA, U (The Indian Journal of Animal Reproduction, 2016)
Using the split sample technique, the semen quality parameters of 36 ejaculates from 3 buffalo bulls were studied after extension in soya milk extender ± superoxide dismutase (SOD) and catalase (CAT). Among sperm defects, tail defects increased (p<0.01) at post- haw stage as compared to post-equillibration stage in antioxidant group. The reduction in acrosomal integrity from post-equilibration to post-thaw stage was observed in both control and treatment groups, however, the reduction was prominent (25%, p<0.01) in control as compared to treatment (13%, p<0.05). The integrity of plasmalemma followed a similar trend as that of acrosomal integrity. Thus, antioxidant fortification prevented reduction in sperm motility and viability which was otherwise observed in non-supplemented group. It is concluded that SOD and CAT enzyme supplementation to soya milk extender can be used to improve post-thaw semen quality in buffalo.